Association between the rs112735431 polymorphism of the RNF213 gene and moyamoya disease: A case-control study and meta-analysis. (October 2016) - Huang, Yanlan; Cheng, Daobin; Zhang, Jiede; Zhao, Weijia
Highlights: We provide evidence of an association between RNF213 polymorphisms and moyamoya disease risk. We used Sanger sequencing after amplification with polymerase chain reaction. Rs112735431 and c.14576G>A are at the same location on the RNF213 gene. Abstract: Ring finger protein 213 (RNF213) gene polymorphisms are thought to be significant in the etiology and pathogenesis of moyamoya disease (MMD). Due to the rarity of MMD patients, their ethnic diversity, and the use of varying methodologies, studies of the association between these polymorphisms and MMD have not been repeatable. This lack of reproducibility affects the strength of the conclusions drawn from their results. We conducted the present case-control study and meta-analysis to provide more precise estimates of the association between the rs112735431 (c.14576G>A) polymorphism and the risk of MMD. A total of 81 MMD patients and 100 healthy controls were enrolled in our case-control study. The RNF213 rs112735431 (c.14576G>A) polymorphism was genotyped using Sanger sequencing after amplification with polymerase chain reaction (PCR). The genetic algorithm (GA) genotype and A allele frequencies of RNF213 rs112735431 (c.14576G>A) (odds ratio, OR = 7.10, 95% confidence interval, CI = 1.51–33.43, p  = 0.006; OR = 9.37, 95% CI = 2.10–41.84, p  < 0.001, respectively) were significantly higher in the MMD group than those in the control group. In our meta-analysis, we assessed a total of eight case-control studies, including 985 patients and 2335 controls. Pooled ORs indicated a significant association between the presence of the rs112735431 (c.14576G>A) polymorphism and MMD risk (dominant model: OR = 74.55, 95% CI = 35.86–154.98, p  < 0.00001). Subgroup analysis based on country and sensitivity analysis verified these results. Our case-control study and meta-analysis both provide evidence of an association between the rs112735431(c.14576G>A) polymorphism in the RNF213 gene and MMD risk.